Language and Orthography as Factors in National Self-Determination of the 19th-Century Croats and Serbs - Sotirović, Vladislav В. (Slavistica Vilnensis, 2002)
This article focuses on the role of language in the 19th-century development of national identities among the Croats and Serbs in Croatia, Dalmatia, Slavonia, Bosnia and Herzegovina. The issues of national self-determination, the ideas and goals of nationhood, and the methods and means for attainment of such goals were of considerable importance for 19th-century Croatian and Serbian intellectuals and politicians. From the early 19th century on, language and orthography were the most significant features of ethnic distinction between the Croats and Serbs.